Landslide susceptibility assessment using frequency ratio technique – A case study of NH67 road corridor in the Nilgiris district, Tamilnadu, India. Issue 1 (April 2021) - Saravanan, S; Istijono, B; Jennifer, J J; Abijith, D; Sivaranjani, S
Abstract: The purpose of this study is to develop landslide susceptibility mapping for NH67 road corridor in the Nilgiris district of Tamilnadu, India, using the Geographic information system (GIS) and multivariate statistical approach. In November 2009, North-East monsoon triggered numerous landslides in the Nilgiris district of Tamilnadu, resulting in a high death toll and considerable damage to property. The landslide-controlling parameters namely lithology, soil type, slope gradient, normalized difference vegetation index (NDVI), proximity to faults, and proximity to road, rainfall and streams were extracted from the spatial database, and the weight coefficient of each factor was computed. Then the landslide hazard was analyzed using the frequency ratio method. For verification of the model, the results of the analyses were then compared with the field verified landslide locations. It was concluded that about 3.86% and 16.23 % of the study area are in the very high and high susceptible zone. Based on this, landslide susceptibility map was then classified as very high, high, moderate, low and very low. In the course of model validation, the results were validated using the ROC curve. The AUC of Frequency ratio model was 67.5%. Therefore, the landslide susceptibility index map of the study area is considered valuable for the decision-makers of the landslide-prone region. This landslide susceptibility map can be used to carry out mitigation measures to reduce the susceptibility associated with landslide hazard.